2010
DOI: 10.2165/11313920-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Audit of Diabetes-Dependent Quality of Life (ADDQoL) [Chinese Version for Singapore] Questionnaire

Abstract: The ADDQoL is reliable and probably valid for assessing QOL among Chinese-speaking Singaporeans with T2DM, although known-groups validity warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 15 publications
4
27
0
Order By: Relevance
“…In the current study, the largest impact of diabetes in all groups was observed on the 'freedom to eat', 'feelings about future', and 'freedom to drink' dimensions. Similar results were reported in earlier studies involving patients with both types of diabetes [13,[22][23][24]. The negative impact from the loss of dietary flexibility on the patients' diabetes-specific QoL refers not only to dietary restrictions around healthy eating and weight loss, but also the need to regularly monitor the relationship between food intake, energy expenditure, and blood glucose level for the majority of patients with diabetes.…”
Section: Discussionsupporting
confidence: 85%
“…In the current study, the largest impact of diabetes in all groups was observed on the 'freedom to eat', 'feelings about future', and 'freedom to drink' dimensions. Similar results were reported in earlier studies involving patients with both types of diabetes [13,[22][23][24]. The negative impact from the loss of dietary flexibility on the patients' diabetes-specific QoL refers not only to dietary restrictions around healthy eating and weight loss, but also the need to regularly monitor the relationship between food intake, energy expenditure, and blood glucose level for the majority of patients with diabetes.…”
Section: Discussionsupporting
confidence: 85%
“…The scale comprises 19 domain‐specific questions where individuals are asked to rate how various aspects of their lives are affected if they do not have diabetes. Both English and Chinese versions of the instrument have been validated locally (Soon et al., ; Wee, Tan, Goh, & Li ). The English version of instrument is culturally appropriate, valid and reliable among Singaporean patients with diabetes (Cronbach's alpha = .94) (Wee et al., ).…”
Section: The Studymentioning
confidence: 99%
“…The English version of instrument is culturally appropriate, valid and reliable among Singaporean patients with diabetes (Cronbach's alpha = .94) (Wee et al., ). The scale in the Chinese language has also demonstrated sound psychometric properties with good internal consistency (Cronbach's alpha = .94) and test–retest reliability (ICC = .95) (Soon et al., ).…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, several have been found to have good psychometric properties [7,8], including the Audit of Diabetes-Dependent Quality of Life (ADDQoL) questionnaire [9,10]. Despite recognition of diabetes-specific quality of life as a useful patient reported outcome, as well as numerous studies designed to investigate the psychometric properties of the ADDQoL [11-13], little work has been done to investigate the factors associated with diabetes-specific quality of life in large scale epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%